The equation of the acute angle bisector of two planes is given by the following formula:
\[
\frac{x - 2y - 2z + 1}{\sqrt{1^2 + (-2)^2 + (-2)^2}} = \pm \frac{2x - 3y - 6z + 1}{\sqrt{2^2 + (-3)^2 + (-6)^2}}
\]
Substituting the coordinates of each point in the options, we find that the point \( (-2, 0, -\frac{1}{2}) \) satisfies the equation of the plane \( P \). Thus, the point lies on the acute angle bisector.
Given the equations of planes:
\[
P_1: x - 2y - 2z + 1 = 0
\]
\[
P_2: 2x - 3y - 6z + 1 = 0
\]
The equation of the plane bisectors is given by:
\[
\frac{x - 2y - 2z + 1}{\sqrt{1^2 + (-2)^2 + (-2)^2}} = \pm \frac{2x - 3y - 6z + 1}{\sqrt{2^2 + (-3)^2 + (-6)^2}}
\]
\[
\frac{x - 2y - 2z + 1}{3} = \pm \frac{2x - 3y - 6z + 1}{7}
\]
Since \( a_1a_2 + b_1b_2 + c_1c_2 = 20>0 \), we choose the negative sign for the acute bisector:
\[
\frac{x - 2y - 2z + 1}{3} = -\frac{2x - 3y - 6z + 1}{7}
\]
\[
7(x - 2y - 2z + 1) = -3(2x - 3y - 6z + 1)
\]
\[
7x - 14y - 14z + 7 = -6x + 9y + 18z - 3
\]
\[
13x - 23y - 32z + 10 = 0
\]
The point \((-2, 0, -\frac{1}{2})\) satisfies this equation.